PENCAPAIAN HASIL PAJAK BUMI DAN BANGUNAN PADA PERIODE SEBELUM DAN SESUDAH PANDEMI COVID-19 - Widya Indah Nurmalasari (Jurnal Bisnis Terapan, 2022)
Abstract The corona virus or Covid-19 pandemic had a major impact on the global economy, including the taxation sector. One of the taxes that has decreased is the land tax and where tax revenue data shows a decrease in the realization of land and building tax revenues. This study aims to find out how to find out the results of taxes and buildings in the period before and before pandemic covid-19. This research used quantitative research. This study used secondary data obtained by documentation studies. The data analysis technique used was paired t-test analysis. The results in this study indicate that there are differences in the results of Land and Building Taxes before and after pandemic covid-19. This shows that the Pandemic COVID-19 can affect taxpayer compliance in paying taxes, which affects the achievement of land and building tax results.